THE EDUCATIONAL SERVICES UKRAINIAN MARKET FORMATION AT THE PRESENT STAGE - NESTORENKO, Tetyana; CHUKURNA, Olena; ROMAKH, Valentyna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the state of the services market in the field of higher education in Ukraine in the period 2010-2020. The authors identify the main factors that affect the dynamics of the number of higher education institutions in Ukraine.A comparative analysis of the distribution and structure of education costs by providers and functions of education in 2019 and 2020 was conducted. The dynamics of changes in the number of higher education institutions in Ukraine for the period 2010-2019, as well as the dynamics of changes in the number of students studying in higher education institutions in Ukraine during this period, were analysed. The distribution of the number of pupils, trainees, and students of educational institutions of Ukraine according to the International Standard Classification of Education was studied. Special attention was paid to the regional aspect of placement of higher education institutions. The uneven location of higher education institutions is justified by the fact that research and educational centres were formed in regions with the most powerful industrial potential.The correlational analysis of factors influencing the dynamics of changes in the number of higher education institutions conducted in the study showed that, in addition to the demographic situation (R=0.88), the average number of full-time employees (R=0.96) has a significant impact on the higher education system. This indicates a reduction in the overall need for highly qualified specialists. Undoubtedly, this is the result of the reduction of certain branches of the economy and the corresponding decrease in the demand for certain specialties from the side of applicants. This is due to the availability of vacancies on the labour market. At the same time, it has been proven that the average monthly salary level and the number of unemployed have no significant impact on the dynamics of changes in the number of higher education institutions.
Keywords: market; educational service; university; analysis; Ukraine